2015
DOI: 10.2903/j.efsa.2015.4063
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety evaluation of the substance zinc oxide, nanoparticles, uncoated and coated with [3‐(methacryloxy)propyl] trimethoxysilane, for use in food contact materials

Abstract: . Scientific Opinion on the safety evaluation of the substance zinc oxide, nanoparticles, uncoated and coated with [3-(methacryloxy)propyl] trimethoxysilane, for use in food contact materials. EFSA Journal 2015;13(4) The zinc oxide nanoparticles are intended to be used as a transparent ultraviolet light (UV) absorber in all types of polyolefins. When coated with [3-(methacryloxy)propyl] trimethoxysilane, the coating is up to 2 % by weight of the zinc oxide. The additive is to be used in the polymer at a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The results revealed greater amounts of zinc released in the acidic solution than in the alcoholic one. Similar results were reported by EFSA [62] where the migration of zinc into 3% (wt/vol) acetic acid was high, up to 17.3 mg/kg, whereas in 10%(vol/vol) ethanol it was up to 80 µg/kg. Furthermore, Ozaki et al [63] evaluated the migration of zinc from food contact plastics into food simulant such as distillate water, 4% acetic acid, and 20% ethanol, finding that zinc migration was higher in 4% acetic acid due to the higher tendency of ionization.…”
Section: Migrationsupporting
confidence: 90%
“…The results revealed greater amounts of zinc released in the acidic solution than in the alcoholic one. Similar results were reported by EFSA [62] where the migration of zinc into 3% (wt/vol) acetic acid was high, up to 17.3 mg/kg, whereas in 10%(vol/vol) ethanol it was up to 80 µg/kg. Furthermore, Ozaki et al [63] evaluated the migration of zinc from food contact plastics into food simulant such as distillate water, 4% acetic acid, and 20% ethanol, finding that zinc migration was higher in 4% acetic acid due to the higher tendency of ionization.…”
Section: Migrationsupporting
confidence: 90%
“…A more recent scientific opinion was given on the use of Zinc oxide in FCM, based on migration results obtained by ICP-MS and ICP-AES. 43 The results indicate that the migration of Zinc occurs to a significant level, while still remaining compliant with the current specific migration limit (SML) for Zinc. Although no proof of the absence of migration in particulate form was given, the panel concluded that the substance does not migrate in nanoform and that the safety evaluation should focus on the migration of soluble ionic zinc.…”
Section: Potential Migration Of Nanomaterialsmentioning
confidence: 66%
“…These are mentioned later. [40][41][42][43][44] Given the few materials currently authorized for use, most of the nanoparticles with potential for improving functionality in plastic packaging materials mentioned in the next chapters are not authorized at EU level, even if their bulk form is authorized. Before these substances can be authorized and used in plastic FCMs, an application for their authorization will need to be submitted containing specific information regarding toxicology and possible exposure.…”
Section: Plasticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration both in nano-form and in ionic-form is major a concern for using NPs for food contact application. 53,54 In a recent opinion issued by EFSA, 55 they evaluated the case of using ZnO NPs for food contact application. LDPE (low-density polyethylene) films containing the maximum use level of the ZnO NPs ZnO NPs were subjected to the standard migration test, and high concentration of Zn 2+ was detected in one food simulant, acetic acid 3% (w/v).…”
Section: Nanomaterials For Food Contact Applicationmentioning
confidence: 99%